Functionalization of Cotton Fabric With Zno/pva for Antibacterial Textile Application - Tan, Lee Yae (2018)
The characteristics of ZnO/PVA on the cotton in term of mechanical strength, surface morph ologies, chemical structure, composition , crystal size of ZnO and antibacterial performance were investigated Range of ZnO compositions ( 0.1, 0.15, 0.2, 0.25 M ) were cooperated with polyvinyl alcohol(PVA) solution (5, 10, 15, 20 g in 200 ml of water) The cotton was padded in the PVA/ZnO solution and dried it at 70 ℃ for overnight It was found that all the treated samples had abundant particles deposit ed on fibers and fibers are attached together. The corresponding EDX result showed carbon, oxygen and zinc elements presented on the treated cotton fabric. From EDX mapping, Zn element was presented uniformly over the cotton fabric. For XRD result, there w as peak at 31.96 31.96°, 34.66 34.66°, 36.46 36.46°, 47.92 47.92° and 56.73 56.73° attributed to the characteri stic peak of ZnO which revealed hexagonal wurtzite structure of the synthesized ZnO NPs. The crystal size of ZnO in the sample was calculated Debye Scherer formula was approxi mately 25~42 nm. Based on FTIR result, the decreasing order of hydroxyl peak of treated samples indicated the bonding was formed between ZnO, PVA and cotton. The antibacterial efficiencies against S.aureus and E.coli increase when ZnO and PVA dosage increase. Generally, t he optimal formulation of antibacterial cotton fabric at 0.25 M ZnO / 15 g PVA as the coated fabric has highest strength against tearing and considerable antibacterial properties against S. aureus and E. coli growth.